The burden of severe asthma in sub-Saharan Africa: Findings from the African Severe Asthma Project - Kirenga, Bruce J; Chakaya, Jeremiah; Yimer, Getnet; Nyale, George; Haile, Tewodros; Muttamba, Winters; Mugenyi, Levicatus; Katagira, Winceslaus; Worodria, William; Aanyu-Tukamuhebwa, Hellen; Lugogo, Njira; Joloba, Moses; et al. (Elsevier Inc, 2024)
Background: Severe asthma is associated with high morbidity, mortality, and health care utilization, but its burden in Africa is unknown. Objective: We sought to determine the burden (prevalence, mortality, and activity and work impairment) of severe asthma in 3 countries in East Africa: Uganda, Kenya, and Ethiopia. Methods: Using the American Thoracic Society/European Respiratory Society case definition of severe asthma, we analyzed for the prevalence of severe asthma (requiring Global Initiative for Asthma [GINA] steps 4-5 asthma medications for the previous year to achieve control) and severe refractory asthma (remains uncontrolled despite treatment with GINA steps 4-5 asthma medications) in a cohort of 1086 asthma patients who had been in care for 12 months and had received all GINA-recommended medications. Asthma control was assessed by the asthma control questionnaire (ACQ). Results: Overall, the prevalence of severe asthma and severe refractory asthma was 25.6% (95% confidence interval [CI], 23.1-28.3) and 4.6% (95% CI, 3.5-6.0), respectively. Patients with severe asthma were (nonsevere vs severe vs severe refractory) older (39, 42, 45 years, P = .011), had high skin prick test reactivity (67.1%, 76.0%, 76.0%, P = .004), had lower forced expiratory volume in 1 second percentage (81%, 61%, 55.5%, P < .001), had lower quality of life score (129, 127 vs 121, P < .001), and had higher activity impairment (10%, 30%, 50%, P < .001). Factors independently associated with severe asthma were hypertension comorbidity; adjusted odds ratio 2.21 (1.10-4.47), P = .027, high bronchial hyperresponsiveness questionnaire score; adjusted odds ratio 2.16 (1.01-4.61), P = .047 and higher ACQ score at baseline 2.80 (1.55-5.08), P = .001. Conclusion: The prevalence of severe asthma in Africa is high and is associated with high morbidity and poor quality of life.
Keywords: Severe asthma burden of severe asthma severe asthma determinants sub-Saharan Africa